The role of kannaki vazakkurai in understanding the culture of sri lankan tamils - Cumaran, E. (university of Jaffna, 2014)
The epic Kaṇṇaki Vazhakkurai and its different versions, Kōvalanār Katai and Cilampu Kūral, are believed to be composed or compiled during the period of Kingdom of Jaffna. These are popular in Batticaloa, Jaffna and Mullaitīvu respectively. Though these three versions may be considered as three different works, there are similarities in their narration, division of chapters and diction; so that it is difficult to distinguish them from one another. The similarities among these three works led the scholars to opine that there ought to be a common source as a pioneer to these versions. This pioneer work may have been adapted by the copyist to suit their respective claims and needs, along with their necessity and creative ability. Though the story of Cilappatikāramis the main theme of this epic, it preserves uniqueness profoundly in its structure, style and the narration of story. Certain portions of the story of this epic are the sole imagination of Sri Lankan author whose name is even now in dark. Kaṇṇaki Vazhakkurai is in abundance in recording the cultural patterns of Sri Lankan Tamils such as art, religion, educational and literary heritage, believes, customs and habits. These valuable facts could not be derived from other sources. As this epic has close association with folk literature, the life style of folks is also brought out obviously. In short Kaṇṇaki Vazhakkurai and its difference versions are the treasure trove who delves deep into the study of Sri Lankan Tamil culture. This paper tries to bring out such cultural aspects in descriptive manner as related in Kaṇṇaki Vazhakkurai.
Keywords: Kaṇṇaki vazhakkurai; Tamil culture; Tamil epic